If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7=-6+x-3
We move all terms to the left:
7-(-6+x-3)=0
We add all the numbers together, and all the variables
-(x-9)+7=0
We get rid of parentheses
-x+9+7=0
We add all the numbers together, and all the variables
-1x+16=0
We move all terms containing x to the left, all other terms to the right
-x=-16
x=-16/-1
x=+16
| −(4x+6.6)+0.1=−(4x+6.6)+0.1= −(3x+1)−3−(3x+1)−3 | | 36/n=0.9/100 | | 4(4x•3x+2)=52 | | 4w4+40w2-44=O | | -2=x5+1 | | 5x-26=119 | | 75/x=0.05 | | 3x+20=6x+8 | | 10/3x=50 | | x8+4=10 | | 2+9g=30 | | -9x+7=25+2(5-x)/x=-4 | | 36=-36-6x | | -5+3=5x | | -15t+25+4t=8t-9 | | 2-4x(2x+3)=8 | | x÷17=22 | | 3x-17=-44 | | 2/z=z/16 | | 9–b=-6 | | 2x+18=4x+11 | | 16=14+3x | | 5(t+6.5)=248.5 | | 2x+18+55+4x+11=180 | | 16/g,g=4 | | 3x+12+144=180 | | 6x+(5x/2)=90 | | 3p+9+3p-63=180 | | 3+2=2x10 | | 14x-13=7x+8 | | 2y+11=30 | | 3+5y-4=0 |